Legal Protection of Children from Interfaith Marriages in Indonesia in the Perspective of Constitutional Court Decision No. 68/PUU-XII/2014 - Setiawati, Ellyna; Noor, Syamhudian; D. Bangas, Karlinae (Journal of Law, Politic and Humanities, 2025)
Constitutional Court Decision No. 68/PUU-XII/2014 is an important milestone in the legal debate regarding the validity of interfaith marriages in Indonesia. Although the decision does not change the normative provisions in Article 2 paragraph (1) of Law No. 1/1974 on Marriage, the implications for the position of children from interfaith marriages are very real. Children born from such relationships often face administrative obstacles, uncertainty of legal status, and potential discrimination in obtaining their basic rights as citizens. This study aims to analyze the juridical implications of the Constitutional Court's decision on the legal protection of children from interfaith marriages, and to encourage the formulation of affirmative policies that guarantee the protection of children's rights as a whole. The research method used is normative juridical with the approach of legislation and analysis of court decisions. The results of the study show that derivative regulations and concrete steps are needed from the state to ensure recognition of the legal status of children, in line with the constitutional principles of child protection and respect for human rights.